Reducing the environmental impact of forestry enterprises - Medvedev Sergey; Zyryanov Mikhail (E3S Web of Conferences)
The paper focuses on examining the environmental impact of forest industry enterprises and developing measures to mitigate it. The authors identify humans as the primary factor influencing the environment in the modern world, with forests serving as a crucial tool for reducing anthropogenic effects. Under such conditions, the activities of forest industry enterprises must be subjected to strict control and analysis, as they represent one of the most significant contributors to deforestation. The research highlights key activities within the industry and identifies the most substantial and critical environmental impacts associated with major processes (types of production). Based on consultations with experts (representatives of large forest industry enterprises) and the conducted study, a list of measures aimed at reducing negative environmental impacts has been developed. The main conclusion emphasizes that increasing attention to sustainable development should be regarded as a fundamental basis for any transformations within the industry aimed at normalizing interactions with the environment.